2013
DOI: 10.1016/j.febslet.2013.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin suppresses AHRR expression through mRNA destabilization

Abstract: Edited by Ivan Sadowski

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…A number of studies have shown that certain metastasis-associated genes with AREs are overexpressed in cancers [34][35][36]. These results are consistent with previous reports that the ARE sequence is important for regulating mRNA stability [32,37]. In the present study, we showed that CRT knockdown suppressed FUT1 mRNA degradation in J82 cells.…”
Section: Discussionsupporting
confidence: 93%
“…A number of studies have shown that certain metastasis-associated genes with AREs are overexpressed in cancers [34][35][36]. These results are consistent with previous reports that the ARE sequence is important for regulating mRNA stability [32,37]. In the present study, we showed that CRT knockdown suppressed FUT1 mRNA degradation in J82 cells.…”
Section: Discussionsupporting
confidence: 93%
“…TTP is an ARE-binding protein that promotes degradation of ARE-containing mRNAs [2,[8][9][10][11][12][13][14]. Brennan et al [1] reported that TTP expression is significantly decreased in many cancers, and it is possible to suppose that the reason for the increased level of E2F1 in tumor cells, which exert various effects on cell growth and tumor development, may result from the low expression of TTP.…”
Section: Discussionmentioning
confidence: 99%
“…miR-mediated gene expression regulation is a well recognized post-transcriptional mechanism that either represses translation and/or destabilizes mRNA transcripts to control protein production (44, 56 -58). Nearly 60% of protein-coding genes are predicted to be targeted by microRNAs and most microRNAs act by base pairing with the 3Ј UTR of the targeted mRNA (59). One gene could potentially be targeted by multiple microRNAs; however, it is unlikely that all of them would be functional at the same time because miRs are expressed in a tissue-and development-specific manner (44, 56 -58, 60).…”
Section: Discussionmentioning
confidence: 99%